Essential oils from three species of Mentha harvested in Sardinia: chemical characterization and evaluation of their biological activity. (29th December 2017) - Fancello, Francesco; Zara, Severino; Petretto, Giacomo Luigi; Chessa, Mario; Addis, Roberta; Rourke, Jonathan P; Pintore, Giorgio
ABSTRACT: The chemical composition, antimicrobial activity, and antioxidant activity of Mentha (M.) requienii, M. pulegium L., and M. aquatica (L.) Huds from Sardinia, Italy, were tested. The chemical composition was determined by Gas Chromatography-Mass Spectrometry (GC-MS) and GC-Flame Ionization Detector (GC-FID) analyses. The antiradical activity was assessed by 2, 2-Diphenyl-1-picrylhydrazyl and antioxidant capacity assay (ABTS) assay and minimal inhibition concentration was determined by microdilution broth analysis. The major components found in M. requienii EO were pulegone, menthone, and limonene; similarly, the major components of M. pulegium EO were pulegone and iso-menthone. By contrast, the major components of the essential oil (EO) from M. aquatica are terpinyl acetate and eucalyptol. The antioxidant activity of M. aquatica EO was higher than that of M. requienii and M. pulegium . The EO from M. requienii had good antifungal and antioxidant activities. In the concentration range tested, the mint EOs did not show any antibacterial activity against Staphylococcus aureus 20231 Deutsche SammLung von Mikroorganismen und Zellkulturen (DSMZ), Salmonella enterica subsp. bongori serovar 66:z41:- 13772 DSMZ, and four strains of Listeria monocytogenes . Lactic acid bacteria (LAB) strains were not inhibited by the EOs tested, with the exception of Lactobacillus brevis, which showed slight sensitivity to M. pulegium and M. requenii EOs. Yeast strains were in general sensitive to the different Mentha EOs tested and were species and strain dependent.